PERFORMING PUBLIC SPEAKING: SELF-EFFICACY AND SPEAKING ANXIETY IN NON-ACADEMIC CLASSROOM CONTEXT - Hasibuan, Anastasia Ronauli (Universitas PGRI Sumatera Barat, 2024)
This study presents the obstacles met by the education ambassadors in performing their communication skill. It is widely known that the recruitment procedure would demand the participants to be well-achieved both in hard and soft skills. Public speaking ability is one of the skills should be mastered so participants might deliver their ideas clearly. However, several variables namely self-efficacy and speaking anxiety are always claimed as important issues to be considered. Fifteen participants were involved as the sample of this study. The Self-Efficacy Questionnaire and Personal Report of Public Speaking Anxiety (PRPSA) Questionnaire were used to collect the data. To obtain the correlation degree between the two discussed variables, the Pearson Product Moment formula was used. The findings of this study would provide beneficial information about the relationship between self-efficacy enhancement and the reduction of speaking anxiety in front of the public for the target sample community.